Bimaadiziwin Native American Approaches to the Mystery of Life - Achiel Peelman (Annales Missiologici Posnanienses, 2014)
Structured around the Ojibwe concept Bimaadiziwin (fullness of life), this study demonstrates how Native American Spirituality contributes to a deeper approach of the mystery of life by its focus on vision, all-inclusive relationships and space. All this is intimately related to the “Spirit world” and symbolized in a unique way  by the Medicine Wheel ritual.